Film Adaptation as an Act of Communication: Adopting a Translation-oriented Approach to the Analysis of Adaptation Shifts - Perdikaki, Katerina (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2017)
Contemporary theoretical trends in Adaptation Studies and Translation Studies (Aragay 2005; Catrysse 2014; Milton 2009; Venuti 2007) envisage synergies between the two areas that can contribute to the sociocultural and artistic value of adaptations. This suggests the application of theoretical insights derived from Translation Studies to the adaptation of novels for the screen (i.e., film adaptations). It is argued that the process of transposing a novel into a filmic product entails an act of bidirectional communication between the book, the novel and the involved contexts of production and reception. Particular emphasis is placed on the role that context plays in this communication. Context here is taken to include paratextual material pertinent to the adapted text and to the film. Such paratext may lead to fruitful analyses of adaptations and, thus, surpass the myopic criterion of fidelity which has traditionally dominated Adaptation Studies. The analysis uses examples of adaptation shifts (i.e., changes between the source novel and the film adaptation) from the film P.S. I Love You (LaGravenese 2007), which are examined against interviews of the author, the director and the cast, the film trailer and one film review.